Human CD3 transgenic mice: preclinical testing of antibodies promoting immune tolerance. - Kuhn, C; You, S; Valette, F; Hale, G; van Endert, P; Bach, J; Waldmann, H; Chatenoud, L (2011)
Monoclonal antibodies have proven to be potent agents to promote immunological tolerance in animal models of autoimmune disease and transplantation. However, optimal clinical application and pharmaceutical development have been limited by the species specificity of therapeutic antibodies, as well exemplified in the case of anti-CD3 antibodies. Compelling evidence in the nonobese diabetic (NOD) mouse, recently translated to clinical autoimmune insulin-dependent diabetes, demonstrates that a short CD3 antibody treatment effectively and durably controls disease progression. We established transgenic mice expressing the human ε chain of the CD3 complex bred onto the NOD background. These mice developed a high incidence of spontaneous autoimmune diabetes and harbored T cells sensitive both in vitro and in vivo to anti-human CD3 antibodies. Treatment of diabetic transgenic mice with otelixizumab, an anti-human CD3 antibody that has proven effective in the clinic, resulted in durable disease remission dependent on transferable T cell-mediated tolerance. This model should enable the evaluation of anti-human CD3 antibodies to determine their potential clinical utility.